Kino powojenne i pułapki naszej świadomości - Tadeusz, Sobolewski (Załącznik Kulturoznawczy, 2015)
The article is a reflection on postwar Polish cinema as a representation of Polish mentality. The analysis is based on the following films: Andrzej Wajda’s Popiół i diament (Ashes and Diamonds) and Marek Koterski’s Wszyscy jesteśmy Chrystusami (We’re All Christs) whose juxtaposition allows to visualize a complex characteristic for Polish consciousness – mournful patriotism, which is associated with messianism. Artistic artifacts are treated as a complementary element that comment on the social reality of specific historical moments.